Determinants of ICT adoption for Digital Inclusiveness in Hill State of Himachal Pradesh-Tourists Perspective - Bhatia, Arun (Atna Journal of Tourism Studies, 2022)
Travel and Tourism have been at the forefront of change from ICT driven technology. The current research aims to find out major determinants and measure the awareness and perception dimensions of ICT importance and usage from tourists’ perspectives of different age categories and education levels visiting the hill town of Dharamshala, Himachal Pradesh India. The research is administered to 100 tourists entering through gateway destinations and visiting Dharamshala. ANOVA and Post-Hoc as a statistical tool indicate non-significant differences among different age groups in terms of online availability of tourism products but significant differences in terms of use of various mobile applications for travel purposes. Our results strongly imply creating a better digital tourism ecosystem with policy measures to help reduce digital disparities in the digital age.